Sintesis dan Karakterisasi Grafena dengan Metode Reduksi Grafit Oksida Menggunakan Pereduksi Zn - Yudha Taufantri; Irdhawati Irdhawati; Ida Ayu Raka Astiti Asih (Syarif Hidayatullah State Islamic University, 2016)
Graphene is a thin material, has a hexagonal two-dimentional lattice and is considered as an interesting material for adsorption process. Nowadays, graphene has been known as a potential material for diverse application, such as adsorbent. In this study graphene was synthesized from graphite. Furthermore, graphene was applied for adsorption of dichloro diphenyl trichloroethane (DDT). Graphene was synthesized by Hummer’s method using hydrothermal and reduced by Zn. The samples were characterized by Scanning Electron Microscope (SEM) and X-Ray Diffraction (XRD) methods. The results of the XRD showed graphene structure in the 2θ, appeared at 23.9369 with interlayer spacing was about 3.71763 Å, compared with graphite oxide structure in the 2θ appeared at 11.2055 with interlayer spacing was about 7.89649 Å. The results of SEM analysis showed graphene has one layer with planar hexagonal structure and seems transparent whose single layer and multi layers. The graphene adsorption was analyzed by using the UV-Visible spectrophotometer. The results indicated the surface area of graphene was shown as 46.8563 m2/g. The amount of DDT adsorbed by graphene during 15 minutes was 7.5859 mg/g. This adsorption mechanism of DDT and graphene might be due to π-π and hydrogen interactions. Keywords: Adsorption, dichloro diphenyl trichloroethane (DDT), graphena. DOI: http://dx.doi.org/10.15408/jkv.v2i1.2233